Why we need a global appellate mechanism for international investment law - Anna Joubin-Bret (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
Establishing an appellate system for investment arbitration for the EU is a main area for the improvement of investor-state dispute settlement. This Perspective suggests that discussions about the desirability and feasibility of an appellate mechanism must be held in a multilateral context and apply to all treaties, not only selected few.
Keywords: 330